La tentación monárquica de Alberdi - Crespo, Horacio (El Colegio de México, A.C., 2015)
This article studies Alberdi’s book Del Gobierno De Sud-América Según Las Miras De Su Revolución Fundamental, which was written between 1863 and 1867 – when a monarchy was imposed in Mexico and it was assumed that many South American countries would follow the same path – and published posthumously in 1896. In this controversial text, the author discussed the convenience and adaptation of monarchy to the necessary conditions for progress in Latin America and showed, in the book’s most provocative reflection, an ambiguous preference for constitutional monarchy over republican government. In the end, Alberdi comes out in favor of a centralist republic with a civilizing mission and a secure grip on power.